Deuki Pratha in Nepal: Problems and Changing Beliefs - K.C., Dipendra Bahadur (Tribhuvan University Journal, 2020)
In the far-western region of Nepal, particularly, in Doti, Baitadi and Dadeldhura, deuki pratha has been practiced as a long established tradition. However, Deuki pratha is considered illegal in Nepal. Deukis are offered to different deities by parents or others (wealthier couples). The reason behind deuki pratha rests on the belief that one’s family gets protection and good favour from the gods. Once offered as Deuki, the girl is not allowed to get married and is devoid of the family support. The major duty of Deuki is to serve the goddess and temple such as cleaning and looking after the temple. The study was conducted in Melauli Municipality of Baitadi district in Sudurpaschim province. This paper aims to highlight the social issues due to deuki in the study area. The study aimed to understand the socio-cultural beliefs of deuki tradition in the changing social and cultural contexts from the gender perspective and development. The study was based primarily on qualitative methods. The study revealed that deuki tradition is still practiced, though it is reported to be declined in the recent years. Unlike in the past, with the growing awareness by the joint efforts of government and non-government organizations’ agencies, practice of Deuki has declined to a great extent but not abolished yet. There was mixed reaction regarding beliefs upon Deuki tradition among the locals. The study found that Deuki women who had been offered to the deity was unknowingly been isolated, when still as a girl and abused from the society as these came at the cost of personal and social life of women. With the growing awareness, and changing society, the locals and the followers of deuki pratha seem to welcome the changes and attitudes towards deuki pratha. However, the social and economic life styles of deukis are at stake. Though, some deukis own some private property, due to the lack of emotional and social support are bound to live forbidden and isolated life. Unlike, in the past, where deukis received reverence and importance, the perception towards deukis has worsened in the study area often belittled as prostitution and the disgrace to the society.